The chitosan cembrane cffectiveness of Anadara granosa clam shells to remove total coliform in greywater - Pradevi Milafitri Farista Ananto; Eri Iva Rustanti; Marlik Marlik; Darjati Darjati; Yudied Agung Mirasa (Intelektual Pustaka Media Utama, 2022)
Clam shell is a solid trash that has a rough texture, difficult to digest, and polluting the environment. Blood clam shells (Anadara granosa) contain chitin, which is converted into antimicrobial chitosan. The purpose of this study was to see the effectiveness of chitosan membrane from blood clam shells in reducing total coliform bacteria in household greywater. This study was carried out using experimental research method design. This research focused on household greywater waste. The chitosan concentrations on the membrane varied between 2.5% and 3.5% with filtration times of 20 and 60 minutes. The Anova Quadratic model test was further used to examine the data. Chitosan was separated from the shell of the blood clam at peak angles of 19.66° and 26.04° according to X-ray diffraction (XRD) characterization. It was obtained that chitosan membrane, with a concentration of 3.5% and a filtering duration of 60 minutes, provided the highest percentage of total coliform bacteria reduction of 99.9%. The conclusion of this study is that blood clam shells used as chitosan membranes can reduce total coliform bacteria in household greywater waste.